FACTORS INFLUENCING CUSTOMER TRUST MEDIATED BY GUANXI IN E-COMMERCES’ FASHION INDUSTRY - Hansopaheluwakan, Scherly; Vinson, Darren; Gosal, Mario Jeremy (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2024)
In an all-digital era, driven by the rapid development of technology, changing people's lifestyles and behavior in activities. One of them is the activity of buying and selling transactions. Nowadays, people tend to use a digital media platform called e-commerce to do transactions. However, even though the adaptation of e-commerce usage continues to increase, the effect after the Covid-19 experienced by business actors is continuing, causing a relatively high decline in profits. This study aims to find ways for businesses to increase their profits through a marketing approach that is oriented towards consumer trust. This research uses a quantitative descriptive method that adopts the Partial Least Square Structural Equation Model (PLS-SEM) with SmartPLS 4.0 software. The data in this study were obtained through an online questionnaire of 186 e-commerce users who have purchased clothing products, live in the Jakarta and Bogor areas, and are between 17-30 years old. This research period was conducted from January 2024 to March 2024. The findings of this research are that E-Service Quality and Customer Engagement has a direct and indirect effect on Customer Trust. The mediator variable used in this study is Guanxi which is a novelty in this study.